2006
DOI: 10.1364/oe.14.008613
|View full text |Cite
|
Sign up to set email alerts
|

Freeform multiphoton excited microfabrication for biological applications using a rapid prototyping CAD-based approach

Abstract: Multiphoton excited polymerization has attracted increasing attention as a powerful 3 dimensional nano/microfabrication tool. The nonlinear excitation confines the fabrication region to the focal volume allowing the potential to achieve freeform fabrication with submicron capabilities. We report the adaptation and use of a computer aided design (CAD) approach, based on rapid prototyping software, which exploits this potential for fabricating with protein and polymers in biologically compatible aqueous environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 23 publications
0
52
0
Order By: Relevance
“…We demonstrated that this spatial information can be used in conjunction with a controlled fabrication technique to create a synthetic scaffold that imitates the organization of the COLIV matrix in the postnatal day 2 mouse ventricle. Because this fabrication technology can be utilized with ECM proteins, 50 this methodology could create ECM protein scaffolds mimicking the in vivo microenvironment of the heart, or other region of interest, during a developmental stage at which the microenvironment elicits cues to its occupying cells to perform a desired function. For example, research groups interested in maintaining, propagating, and encouraging differentiation of cardiac progenitors might consider utilizing the ECM blueprint defined at E16.5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We demonstrated that this spatial information can be used in conjunction with a controlled fabrication technique to create a synthetic scaffold that imitates the organization of the COLIV matrix in the postnatal day 2 mouse ventricle. Because this fabrication technology can be utilized with ECM proteins, 50 this methodology could create ECM protein scaffolds mimicking the in vivo microenvironment of the heart, or other region of interest, during a developmental stage at which the microenvironment elicits cues to its occupying cells to perform a desired function. For example, research groups interested in maintaining, propagating, and encouraging differentiation of cardiac progenitors might consider utilizing the ECM blueprint defined at E16.5.…”
Section: Discussionmentioning
confidence: 99%
“…50 The same region was imaged in 20 serial sections from a postnatal day 2 ventricle labeled with the anti-COLIV antibody. Antibody labeling and subsequent imaging were performed as described above.…”
Section: Fabrication Based On Ecm Blueprintmentioning
confidence: 99%
See 1 more Smart Citation
“…72,73 Because Rose Bengal displayed a low solubility at acidic pH, where collagens have the highest solubility, another photoinitiator that is soluble at acidic pH was considered. Consequently, they reported a newly synthesized benzophenone dimer that could act as a photoinitiator for both BSA and collagen cross-linking.…”
Section: Cross-linking Of Natural Hydrogelsmentioning
confidence: 99%
“…In recent years, three-dimensional (3D) micro-/nanofabrication techniques have attracted increasing attention, due to their promise in a wide range of applications including integrated optics, 1,2 plasmonics, 3,4 microbiology 5,6 and microelectromechanical systems. [7][8][9][10][11] Similar to 3D fabrication at macroscopic scales, 3D micro-/nanofabrication generally entails two fundamental approaches: additive and subtractive processes.…”
Section: Introductionmentioning
confidence: 99%